The climatology of lightning producing large impulse charge moment changes with an emphasis on mesoscale convective systems - Beavis, Nicholas, author; Rutledge, Steven A., advisor; Schumacher, Russ S., committee member; Lyons, Walter A., committee member; Lang, Timothy J., committee member; Eykholt, Richard E., committee member (Colorado State University. Libraries, 2013)
The use of both total charge moment change (CMC) and impulse charge moment change (iCMC) magnitudes to assess the potential of a cloud-to-ground (CG) lightning stroke to induce a mesospheric sprite has been well described in literature. However, this work has primarily been carried out on a case study basis. To complement these previous case studies, climatologies of regional, seasonal, and diurnal observations of large-iCMC discharges are presented. In this study, large-iCMC discharges for thresholds > 100 and > 300 C km in both positive and negative polarities are analyzed on a seasonal basis using density maps of 2° by 2° resolution across the conterminous U.S. using data from the Charge Moment Change Network (CMCN). Also produced were local solar time diurnal distributions in eight different regions covering the lower 48 states as well as the Atlantic Ocean, including the Gulf Stream. In addition, National Lightning Detection Network (NLDN) cloud-to-ground (CG) flash diurnal distributions were included. The seasonal maps show the predisposition of large positive iCMCs to dominate across the Northern Great Plains, with large negative iCMCs favored in the Southeastern U.S. year-round. During summer, the highest frequency of large positive iCMCs across the Upper Midwest aligns closely with the preferred tracks of nocturnal mesoscale convective systems (MCSs). As iCMC values increase above 300 C km, the maximum shifts eastward of the 100 C km maximum in the Central Plains. The Southwestern U.S. also experiences significant numbers of large-iCMC discharges in summer, presumably due to convection associated with the North American Monsoon (NAM). The Gulf Stream is active year round, with a bias towards more large positive iCMCs in winter. Diurnal distributions in the eight regions support these conclusions, with a nocturnal peak in large-iCMC discharges in the Northern Great Plains and Great Lakes, an early- to mid-afternoon peak in the Intermountain West and the Southeastern US, and a morning peak in large-iCMC discharge activity over the Atlantic Ocean. Large negative iCMCs peak earlier in time than large positive iCMCs, attributed to the maturation of large stratiform charge reservoirs after initial convective development. Results of eight case studies of Northern Great Plains MCSs using the NMQ National Radar Mosaic dataset are also presented. Thresholds described above were used to disseminate iCMC discharges within the MCSs. The radar analysis algorithm on a 5-minute radar volume basis included convective-stratiform partitioning, association of iCMCs and CGs to their respective storms, and statistical analysis on large (100-300 C km) and sprite-class (>300 C km) iCMC-producing storms. Results from these case studies indicated a strong preference of sprite-class iCMCs to be positive and located in stratiform-identified regions. A 2-3 hour delay in the maximum activity of sprite-class iCMCs after the maximum large iCMC activity was noted, and was strongly correlated with the maximum areal coverage of stratiform area. A loose correlation between more frequent sprite-class iCMC production and larger stratiform areas was noted, suggesting that larger stratiform areas are simply more capable, not more likely, to produce high sprite-class iCMC rates. Enhanced maximum convective echo heights corresponded to enhanced sprite-class iCMC activity in stratiform areas, attributed in part to enhanced charge advection from the convective line. In situ charging was also presumed to have a significant role in charge generation leading to sprite-class iCMC discharges in stratiform regions.
Keywords: sprite; MCS; mesoscale convective system; charge moment change; lightning